Selected features of the medical langauge – terminology, standardization, medical genres and genre shift - Karwacka, Wioleta (Specialized Languages in Intercultural Communication, 2020)
This article discusses selected features of the medical language with special emphasis on Polish and English. The first discussed feature is medical terminology, in particular: Greek and Latin influences, eponyms and acronyms. The medical language is a controlled one, which is another aspect presented in this article. The next characteristic feature includes conventions related to particular medical genres. Finally, genre shift is briefly discussed.